Observing mother-child interaction in a free-play vs. a structured task context and its relationship with preterm and term born toddlers' psychosocial outcomes - Krijnen, L. J. G; Verhoeven, M.; van Baar, A. L. (Frontiers in Child and Adolescent Psychiatry, 2023)
High quality of mother-child interaction is associated with better psychosocial outcomes in children. However, this association might depend on the context in which mother-child interaction is observed as well as specific child characteristics. In this study, we examine differences in the assessment of mother-child interaction in a free-play and a structured task context. In addition, it will be investigated whether the behaviors per context are differently associated with preterm versus term born toddlers’ psychosocial outcomes. A total of 201 Dutch mother-child dyads participated in the study, of whom 108 children were moderate to late preterm (MLP) and 93 were born at term. Mother-child interaction was observed in a free-play and a structured task context when the child was 18 months of (corrected) age. Six subscales of mother-child interaction were assessed using the Coding Interactive Behavior scheme. Psychosocial outcomes were assessed at 24 months of (corrected) age. Mother-child interaction was reliably assessed (α > .60) in each context, except for tense interaction during free-play (α = .41). Compared to the free-play context, during the structured task, more child’s negative affect, tense interaction and active mother and child engagement was observed in MLP and term born children, and less dyadic synchrony in MLP children (p’s < .01). Only during a structured task and for term born children, active mother and child engagement was related to less psychosocial difficulties. Only during free-play and for MLP children, active mother and child engagement was related to less externalizing behaviors. Dyadic synchrony during a structured task was associated with less social-emotional difficulties in both groups, and dyadic synchrony during free-play was only associated with less social-emotional difficulties in term born children (all p’s < .05). The structured task context elicited more varied behaviors than the free-play context. With the observations in the structured task context, more associations with children’s social-emotional difficulties and internalizing and externalizing problems were found than with the observations in the free-play context. Mother-child interactions characterized by active, engaged and synchronous behaviors were associated with better psychosocial outcomes in toddlers, especially for children born at term and when observed during a structured task.